The Influence of Social Media Utilization, Digital Campaigns, and Advertising Expenditures on Increasing Company Revenue - Rinaldi Rinaldi; Raja Bayu Ikhsan Riansyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Technology and social media development have enabled companies to promote products more effectively, enhance interactions with customers, and increase revenue. This study analyzes the impact of Social Media Utilization, Digital Campaigns, and Advertising Expenditure on the increase in company revenue. This research employs purposive sampling techniques with 74 respondents consisting of marketing managers and marketing staff from companies who are directly involved in digital marketing strategies and advertising expenditure. Data were collected through a Likert scale-based questionnaire and analyzed using multiple linear regression with SPSS 22 to test the influence of Social Media Utilization, Digital Campaigns, and Advertising Expenditure on the Increase in Company Revenue. The study shows that Social Media Utilization, Digital Campaigns, and Advertising Expenditure significantly affect the Increase in Company Revenue. Social media usage has the greatest influence, followed by digital campaigns and optimal advertising expenditure. These three variables can explain 56.7% of the variation in revenue increase, while other factors outside the scope of the research influence the remaining 43.3%.